Hemangiomatous Ameloblastoma: A Rare Variant - Rajmohan, M; Prasad, H; Shanmugasundaram, N; Thangam, P Tamil; Ilayaraja, V; Anuthama, K (Journal of Orofacial Research, 2014)
Ameloblastoma is a true neoplasm of enamel organ type tissue. It is the most common odontogenic neoplasm with more frequency in the mandible. A 20 years old male patient presented with a swelling in the right side of the mandible of 10 months duration. Orthopantomograph revealed multilocular radiolucency extending from the region of 46 to the condyle. Incision biopsy revealed features of plexiform ameloblastoma. Numerous vascular spaces of varying size were seen throughout the stroma. Excision biopsy also revealed similar findings. Based on these findings, a diagnosis of hemangiomatous plexiform ameloblastoma was made. Hemangiomatous ameloblastoma (HA) is still a controversial entity, with some pathologists ruling it out as a  separate lesion. This paper discusses the possibility that HA might be an aggressive variant of ameloblastoma and reviews relevant literature.